Conceptualising Odova (Alias) Within the Context of African Oral Performance - Adjeketa, Blessing; Odunze, Josephine Awele; Onyekaba, Cornelius Eze; Enita, Godfrey O. (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
Africa's communal nature is deeply rooted in its cultural heritage, with social activities like festivals and ceremonies incorporating performative elements for education and cultural transmission. However, Westernization threatens these valuable oral traditions, leading to their marginalization. Preserving these traditions is crucial for maintaining African identity and cohesion. The study explores the concept of Odova (alias) within the Okpe nationality of Nigeria, a call-and-response performance demonstrating authority, marking identity, and transmitting cultural knowledge. The research combines interviews and ethnographic research within Okpe communities to understand how these traditions are sustained across generations. The study highlights the profound connection between orality and cultural significance, illustrating how Odova encapsulate individual identity, achievements, and social standing. These aliases are dynamic elements within Okpe traditional performances, serving as vehicles for transmitting history, values, and societal norms. Through the study of Odova, we gain insights into the complex interplay between language, performance, and cultural identity in Okpe society, underscoring the enduring power of oral traditions in preserving and celebrating cultural heritage. Keywords: Call-and-response, Cultural preservation, Odova, Okpe traditions, Oral performances